Research Review: Early Childhood and the ‘Intergenerational Cycle of Domestic Violence’ - Devaney, John (2019)
This rapid evidence review was commissioned by the NSPCC to increase our understanding of the complex surrounding the evidence about domestic violence and the potential for this to impact on children's own violent behaviour, and any evidence of effectiveness of targeted interventions aimed at young families